2013
DOI: 10.5539/ijbm.v8n24p48
|View full text |Cite
|
Sign up to set email alerts
|

The CSFs, Quality Governance, BPR Performance and Gaining Competitive Advantage

Abstract: Business process reengineering (BPR) is a popular management approach, which enables organizations to conduct substantial business and technological improvements. Successful implementation of BPR can assist organizations to change their old-fashioned practices into innovative processes through reorganizing and eliminating some processes and/or finding innovative ways to conduct business activities. Studies have shown, successful BPR implementation can. 1) create higher customer satisfaction, 2) increase produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The critical challenges generated based on the responses from the project role groups belonging to the case organization highlighted the significance of the study. In particular, Mishra and Mishra (2011) pointed out that one of the main challenges specific to oil and gas is that the design, development, testing, and building of such complex interfaces are time-consuming (Smith, Meade, Wolf, & Song, 2013;Yen & Sheu, 2004). One of the significant challenges among the top 12 was interface issues, which highlighted this critical challenge in the oil and gas industry.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…The critical challenges generated based on the responses from the project role groups belonging to the case organization highlighted the significance of the study. In particular, Mishra and Mishra (2011) pointed out that one of the main challenges specific to oil and gas is that the design, development, testing, and building of such complex interfaces are time-consuming (Smith, Meade, Wolf, & Song, 2013;Yen & Sheu, 2004). One of the significant challenges among the top 12 was interface issues, which highlighted this critical challenge in the oil and gas industry.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…Likewise, Smith et al (2013) found that BPR studies conducted by Edward and Mbohwa (2013). Fu et al (2013) reported that to implement BPR successfully, leadership needs to create a culture that embraces change.…”
Section: Literature Reviewmentioning
confidence: 93%
“…From the above discussions, it is evident that both TQM and BPR are linked to knowledge, leadership, organizational culture and organizational learning (Arh and Blazic, 2012; Al-Bourini et al , 2013; Smith et al , 2013). These researchers also confirm that knowledge, leadership, organizational culture and organizational learning can change during the BPR and TQM implementation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional insights on how BPM training can be leveraged as a competitive advantage over competitors, and benchmarking of BPM training, are areas that could shed more light to the varied uses of BPM training. Some authors have regarded training as having an important link to HRM aspects such as knowledge creation (Birasnav and Rangnekar, 2010), diminishing resistance to change (Smith et al, 2013), increasing the levels of people's readiness for business process reengineering (Habib, 2013), in enhancing peoples' attitude to change (Margherita and Petti, 2010) and in embedding BPM cultural values into an organization (Schmiedel et al, 2013). It is also regarded as a success factor for change projects (Baumöl, 2015), business process outsourcing (Mahmoodzadeh et al, 2009) and process-based management (Balzarova et al, 2004, as cited in Willaert et al, 2007.…”
Section: Papermentioning
confidence: 99%